When the Room Is Spinning: Experience of Vestibular Neuritis by a Neurotologist - Kim, Ji-Soo (Frontiers in Neurology, 2020)
Vestibular neuritis (VN) is the most common cause of acute prolonged spontaneous vertigo, and is characterized by acute unilateral vestibular hypofunction, probably due to inflammation of the vestibular nerve. VN is diagnosed at the bedside when there is spontaneous horizontal-torsional nystagmus beating away from the side of the lesion, abnormal head impulse tests for the semicircular canals involved on the lesion side, and when other neurological symptoms and signs are absent. Here, as a neuro-otologist, I describe my experience during an attack of VN and discuss how it may help physicians to better understand why and what a patient feels during attacks of vertigo.